On comparison of some variation of ranked set sampling - Kamarulzaman Ibrahim (Universiti Kebangsaan Malaysia, 2011)
Many sampling methods have been suggested for estimating the population median. In the situation when the sampling units in a study can be easily ranked than quantified, the ranked set sampling methods are found to be more efficient and cost effective as compared to the simple random sampling. In this paper, the superiority of several ranked set sampling methods over the simple random sampling are illustrated through some simulation study. In addition, some new research topics under ranked set sampling are suggested.